Stress Among Undergraduate Medical Students in a Medical College of Nepal - Paudel, Ajita; Koirala, Naba Raj; Upadhyay, Shikha; Mishra, Rajan; Karki, Dikshya; Koirala, Akishika (Birat Journal of Health Sciences, 2024)
Introduction: Medical education imposes significant stress on students, affecting their psychosocial well- being and academic performance. However, the stressor and its impact vary from person to person. Objectives: To assess stress level and its association with years of medical education. Methodology: This was a cross-sectional study conducted in medical students at Birat Medical College Teaching Hospital. Demographic and academic details were collected using semi-structured proforma. The Medical Student Stressor Questionnaire was used to assess Academic Related Stressor (ARS), Intrapersonal and Interpersonal related stressor (IRS), Teaching and Learning Related Stressor (TLRS), Social Related Stressor (SRS), Drive and Desire Related Stressor (DRS) and Group Activities Related Stressor (GARS). Results: A total of 324 students were enrolled in the study out of which 181(55.86%) were males and 143 (44.14%) were females. The age of the participants ranged from 18 to 27 years (Mean = 22.05 years, SD = 1.8). Majority of participants were from first year (29%) followed by second year (21.6%). About 47% of the participants had high level of ARS, 63.27% participants had moderate level IRS, 51.23% participants had moderate level TLRS, 56.79% participants had moderate level SRS, 46.9% participants had moderate level DRS whereas 42.28% participants 3 had mild level of DRS. Significant association was found among different domains of stressors and years of medical education. Conclusion: Results from our study showed that all the students had some form of stress ranging from mild to severe. This emphasizes on providing mental health support to medical students.